Variability in the Statistical Properties of Continuous Seismic Records on a Network of Stations and Strong Earthquakes: A Case Study from the Kamchatka Peninsula, 2011–2021 - Galina Kopylova; Victoriya Kasimova; Alexey Lyubushin; Svetlana Boldina (Applied Sciences, 2022)
A study of spatiotemporal variability and synchronization effects in continuous seismic records (seismic noise) on a network of 21 broadband seismic stations on the Kamchatka Peninsula was carried out in connection with the occurrence of strong earthquakes, M = 7.2–8.3. Data of 1-min registrations of the vertical movements velocity Earth’s surface were used for constructing time series of daily values of the generalized Hurst exponent α*, singularity spectrum support width ∆α, wavelet-based spectral exponent β, and minimum normalized entropy of squared orthogonal wavelet coefficients En for all stations during the observation period 2011–2021. Averaged maps and time-frequency diagrams of the spectral measure of four noise parameters’ coherent behavior were constructed using data from the entire network of stations and by groups of stations taking into account network configuration, volcanic activity and coastal sea waves. Based on the distribution maps of noise parameters, it was found that strong earthquakes arose near extensive areas of the minimum values of α*, ∆α, β, and the En maximum values advance manifestation during several years. The time-frequency diagrams revealed increased amplitudes of the spectral measure of the coherent behavior of the 4-dimensional time series (synchronization effects) before three earthquakes with Mw = 7.5–8.3 over months to about one year according to observations from the entire network of stations, as well as according to data obtained at groups of continental and non-volcanic stations. A less-pronounced manifestation of coherence effects diagrams plotted from data obtained at coastal and volcanic groups of stations and is apparently associated with the noisiness in seismic records caused by coastal waves and signals of modern volcanic activity. The considered synchronization effects correspond to the author’s conceptual model of seismic noise behavior in preparation of strong earthquakes and data from other regions and can also be useful for medium-term estimates of the ...